The potential of utilizing food waste as pig feed in Sentani District, Jayapura Regency - Rumbrapuk, Max; Rumetor, Sientje Daisy; Saragih, Evi W. (Fakultas Peternakan Universitas Papua, 2025)
The increasing demand for sustainable livestock feed sources has sparked interest in the reutilization of food waste. This study aims to assess the quantity, types, and nutritional content of food waste generated from households, restaurants, and hotels in Sentani District, Papua, Indonesia, and evaluate its potential as an alternative feed for pigs. A descriptive mixed-method approach was employed, involving field surveys, structured interviews, and laboratory analysis. Daily food waste production was highest in hotels (33.00 kg/day), followed by restaurants (8.64 kg/day) and households (5.33 kg/day). Nutritional analysis showed that dry matter content was highest in restaurant waste (29.74%), moderate in hotel waste (28.03%), and lowest in household waste (17.19%). The study reveals that hotel and restaurant waste is richer in nutrients and more consistently available, making it a more suitable feed source. However, high moisture content in household waste necessitates prompt handling and processing. These findings highlight the potential of food waste to enhance feed sustainability, reduce costs, and support environmentally responsible livestock practices in rural Papua New Guinea.